Analisis Antrian dan Servqual terhadap Kepuasan Konsumen pada Perbankan Swasta Kota Bekasi - Haliawan, Prillia; Setyanto, Eddy (JURNAL MANAJEMEN BISNIS TRI BHAKTI, 2024)
The purpose of this study is to analyze the effect of queuing and service quality (servqual) on consumer satisfaction in the private banking service industry in Bekasi City. This study uses a quantitative descriptive approach in analyzing and describing the influence of queuing variables and service quality variables (servqual) as independent variables on dependent variables (customer satisfaction). Sampling from the population using random sampling technique. The samples obtained are then tested using the SPPS version 26 tool which includes validity tests, reliability tests, classical assumption tests and hypothesis tests. Analysis of data processing shows that the queue variable (independent variable) has a partial effect with a positive direction expressed with a t-count value of 5.254 > t-table 1.984 and significant (0.000 < 0.05) to consumer satisfaction (dependent variable). For the variable of service quality (independent variable) partially also affects in a positive direction where the value of t-count is 16.655 > t-table 1.984 and significant (0.000 < 0.05) to consumer satisfaction. Both independent variables (queues and service quality) simultaneously affect the dependent variable (customer satisfaction) where F-count is 13.890 > F-table is 3.09 and significant is 0.000 < 0.05.